Teknologi Informasi Dalam Pendidikan: Sejarah dan Implikasinya Terhadap Pembelajaran di Era Digital - Tiara Tirta Dewi; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Education has become one of the fields that has taken maximum advantage of the Information Technology paradigm, especially in the current digital era. specifically explores the historical path that information technology in learning has taken to get to where it is today and what it portends for learning in the 21st century. By examining the evolution from traditional educational media to internet-based instruction and learning and cloud-based 'virtual' learning environments, this article argues that information technology has changed modes of learning, increased accessibility of resources, and personalized instruction for the better. it goes on to discuss the next challenge: the 'new' digital divide issues that may emerge, and whether teachers can make productive use of the technology provided to them in their classrooms. Thus, this research hopes that readers will appreciate the importance of embracing technology in advancing more inclusive and dynamic learning innovations in this digital era.